Quantifying the impact of climate change and human activities on runoff at a tropical watershed in South China - Li, Dan; Zhu, Lirong; Xu, Wen; Ye, Changqing (Frontiers in Environmental Science, 2022)
Different regions exhibit different response patterns of hydrological process changes under changing environments. The hydrological response mechanism of underlying surface changes in tropical rainforest regions remains uncertain, so there is an urgent need to study the causes of hydrological changes in typical tropical watersheds. The sequential clustering analysis and Pettitt-Mann-Whitney test were employed to detect abrupt change points of runoff series for the Wanquan River Basin in the tropics, and the series was then divided into pre-impact period (1967-1990) and post-impact period (1991-2014). And the Soil and Water Assessment Tool (SWAT) model was used to simulate the runoff to quantify the impact of climate change, land use change and other human activities on runoff, which the latter two collectively referred to as “human activities” in this study. The findings reveal: (1) runoff series showed an abrupt change and a downward trend around the year 1990; the SWAT model has a good simulation in the Wanquan River Basin during the pre-impact period; the coefficients of determination (R2) for the calibration and validation periods are both 0.91, and the Nash-Sutcliffe model efficiency coefficients (NSE) for the calibration and validation periods are 0.89 and 0.86, respectively. (2) There was a considerable change in land use between 1967 and 2014, as evidenced by a decrease of 29.54% in natural forest and an increase of 54.90% in rubber. These land use changes were mostly caused by the transformation of tropical rainforests into rubber forests and orchards. (3) Runoff declined in the post-impact period from the pre-impact period, with climate change, land use change, and other human activities contributing 44.05%, 10.83%, and 45.12% to the runoff change, respectively. The conversion of tropical rain forests to rubber forests and orchards has indirectly led to a reduction in runoff. These results can provide a reference for understanding the evolution of water cycle for other tropical rivers.